2021
DOI: 10.1007/s11069-021-05055-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal meteorological drought assessment: a case study in south-east Australia

Abstract: An understanding on different aspects of droughts is crucial for effective water resources management. Australia has experienced notable droughts in recent years. The present study utilises Effective Drought Index (EDI) and Standardized Precipitation Index (SPI) based on six time horizons (3, 6, 9, 12, 24, and 36 months) to evaluate drought parameters such as magnitude, duration, and intensity with their onset and end in south-east Australia using data from 45 rainfall stations. Maximum drought quantities det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Since the medium-term ATR trends, between 1970 and 2019, show a significantly negative trends in the region and we know that the severity of recent drought aggravated over the past two-three decades due to changes in rainfall and temperatures (Gallant et al 2007;Murphy and Timbal 2008;Timbal 2009;Ummenhofer et al 2009;Dey et al 2019). Furthermore, Yildirim and Rahman (2021) found maximum drought quantities (the longest duration, biggest magnitude, and highest intensity) of shortand long-term droughts in various rainfall districts in southeastern Australia between 2013 and 2019. It can be concluded that the study area suffered from a prolonged drought till 2019.…”
Section: Drought Trend Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since the medium-term ATR trends, between 1970 and 2019, show a significantly negative trends in the region and we know that the severity of recent drought aggravated over the past two-three decades due to changes in rainfall and temperatures (Gallant et al 2007;Murphy and Timbal 2008;Timbal 2009;Ummenhofer et al 2009;Dey et al 2019). Furthermore, Yildirim and Rahman (2021) found maximum drought quantities (the longest duration, biggest magnitude, and highest intensity) of shortand long-term droughts in various rainfall districts in southeastern Australia between 2013 and 2019. It can be concluded that the study area suffered from a prolonged drought till 2019.…”
Section: Drought Trend Analysismentioning
confidence: 99%
“…Gallant et al (2013) found that the average drought lengths in parts of southeast Australia have shown a significant increase since 1911. Furthermore, southeast Australia was exposed to some of most intense drought events in terms of duration, magnitude and severity, between 2013 and 2019 (Yildirim and Rahman 2021). King et al (2020) found that southeastern Australia, in particular Murray-Darling Basing, had been in severe drought since 2017.…”
Section: Introductionmentioning
confidence: 99%
“…This index has been used for different applications including climate research for different regions and seasons. Such studies include over Europe (e.g., Cammalleri et al, 2022; Lloyd‐Hughes & Saunders, 2002; Spinoni et al, 2014), Asia (e.g., Aadhar & Mishra, 2017; Sharma et al, 2021; Zhai et al, 2010), Northern America (e.g., Agnew, 2000; Sung & Stagge, 2022), South America (e.g., Sgroi et al, 2021; Zanvettor & Ravelo, 2000), Australia (e.g., Mpelasoka et al, 2008; Yildirim & Rahman, 2022) and Africa (e.g., Gader et al, 2022; Naumann et al, 2012; Ntale & Gan, 2003).…”
Section: Methodsmentioning
confidence: 99%